APPLYING WHOLE LANGUAGE APPROACH AND PUBLIC SPEAKING ACTIVITY IN SMART EKSELENSIA HIGH SCHOOL - Lisa Rosaline; Amru Asykari (English Review: Journal of English Education, 2013)
Abstract: Whole Language Approach (WLA) is the approach to learn language that focus on the real communication, reading and writing in the fun learning environment context (Richard and Rodgers 2001). The teachers of WLA believe that the students should learn the materials in unity. This study involved 102 of 3 153rd Â to 5 Â year grade students of Smart Ekselensia High School, Bogor, Indonesia. The public English speaking activity has been held for 6 months. The public speaking can be in form of storytelling, general speech, and religious speech. Before the students performed the public speaking, they had to prepare the material such as a story or a book summary. Instrument used to obtain the data were questionnaires and interviews aimed at gathering statistical data and open responses about what students think and feel about the public speaking activity. Based on the ï¬ndings, basically students can improve their four language skills although it still cannot be seen directly. According to the result of the interview, some students suggest the whole language approach and public speaking be continued. They also suggest the frequency be added more in order to encourage them to speak English and create a good English environment.Keywords: Whole Language Approach, Public Speaking, Competence Standard Curriculum.